2014
DOI: 10.1155/2014/815424
|View full text |Cite
|
Sign up to set email alerts
|

Novel Psychoactive Substances in Young Adults with and without Psychiatric Comorbidities

Abstract: Objective. Comorbidities between psychiatric diseases and consumption of traditional substances of abuse (alcohol, cannabis, opioids, and cocaine) are common. Nevertheless, there is no data regarding the use of novel psychoactive substances (NPS) in the psychiatric population. The purpose of this multicentre survey is to investigate the consumption of a wide variety of psychoactive substances in a young psychiatric sample and in a paired sample of healthy subjects. Methods. A questionnaire has been administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
67
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(72 citation statements)
references
References 29 publications
4
67
0
1
Order By: Relevance
“…Alcohol use was also associated with the use of novel psychoactive substances, a new trend exacerbated by the presence of alcohol (8). Moreover, students with problematic alcohol use are less likely to seek professional help for their mental health problem (9).…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use was also associated with the use of novel psychoactive substances, a new trend exacerbated by the presence of alcohol (8). Moreover, students with problematic alcohol use are less likely to seek professional help for their mental health problem (9).…”
Section: Introductionmentioning
confidence: 99%
“…Continuing this trend, during 2015, a total of 100 new substances (i.e., cathinones, cannabinoids, phenethylamines, opioids, tryptamines, benzodiazepines, arylalkylamines, and other groups) were reported for the first time to the EU Early Warning System, bringing the total number of new substances monitored to more than 560, with more than 380 (70%) of these detected in the last 5 years alone and with two new substances detected every week (EMCDDA, ). With increased availability, harms have increased, such as acute, sometimes fatal, poisonings (Chiappini et al, ; Loi et al, ; Dines et al, ; Zawilska & Andrzejczak, ; Bersani et al, ; Schifano et al, ), harms associated with injecting drugs (Hope et al, ), and the possibility to develop psychiatric symptoms (Martinotti et al, ; Martinotti et al, ; Bersani et al, ). Beside acute toxicological effects, many NPS seem to have addictive properties (Miliano et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…There is no published UK research on the use and impact of these substances on patients under the care of mental health services. An Italian study compared NPS use in psychiatric patients with a random sample of healthy subjects and found that NPS use was significantly higher in psychiatric patients than in healthy individuals 5. This is in continuity with the increased prevalence of drug use in mental health service users compared with the general population 6 7…”
Section: Introductionmentioning
confidence: 93%